Questions Raised by the Covid-19 Pandemic for Pastoral Activity in the Irish Context - Duffy, Eugene (2021)
The Covid 19 pandemic has revealed many fault lines in the Church in Ireland. The ageing of its congregations, priests and lay ministers; the weaknesses of its synodal structures at parish level; an over reliance on the clergy to provide leadership; too many expectations are placed on the public liturgies at the expense of good catechesis and forms of popular piety; a failure to reckon with the greatly secularised nature of contemporary Irish society. Yet there are new opportunities for renewal presenting themselves through the crisis.
La pandémie de Covid 19 a révélé de nombreuses failles dans l’Église en Irlande: le vieillissement de ses communautés, des prêtres et des ministres laïcs, les faiblesses de ses structures synodales au niveau des paroisses, une confiance excessive dans le clergé pour assurer le leadership, des attentes trop importantes envers les liturgies publiques au détriment de la bonne catéchèse et des formes de piété populaire, un manque de prise en compte de la nature fortement sécularisée de la société irlandaise contemporaine. Pourtant, à travers la crise, de nouvelles possibilités de renouveau apparaissent.
Die Covid-19-Pandemie hat viele Bruchlinien in der Kirche in Irland offengelegt. Die Überalterung der Gemeinden, der Priester und der Laien; die Schwächen der synodalen Strukturen auf Gemeindeebene; ein übermäßiges Vertrauen auf die Leitung durch den Klerus; zu hohe Erwartungen an die öffentlichen Liturgien auf Kosten einer guten Katechese und Formen der Volksfrömmigkeit; ein Versagen, sich mit der stark säkularisierten gegenwärtigen irischen Gesellschaft auseinanderzusetzen. Jedoch ergeben sich durch die Krise Möglichkeiten der Erneuerung.